2002
DOI: 10.1177/002246690203500401
|View full text |Cite
|
Sign up to set email alerts
|

Weighing the Benefits of Anchored Math Instruction for Students with Disabilities in General Education Classes

Abstract: The purpose of this study was to examine the effectiveness of enhanced anchor instruction and traditional problem instruction in improving the problem-solving performance of 42 seventh-grade students with and without disabilities in general education classrooms. Qualitative research strategies embedded in a quasi-experimental, nonequivalent control-group design permitted investigators to describe and compare the problem-solving performances of individual students with disabilities in general education settings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 36 publications
6
94
0
1
Order By: Relevance
“…For a variety of philosophical, legal, social, budgetary, and educational reasons, special educators are advocating for students with disabilities to be educated alongside their peers without disabilities in general education classrooms. Although some authors have found that the performance of students with disabilities in inclusive classrooms equals or surpasses their performance in pullout settings (e.g., Rea, McLaughlin, & Walther-Thomas, 2002), the results of this study support other authors who warn that even in general education classes with small groups of students, some students with disabilities do not get the individualized attention they need to understand the academic content (Baxter, Woodward, Voorhies, & Wong, 2002, Bottge et al, 2002Kauffman, 1999).…”
Section: Practical Significancesupporting
confidence: 75%
See 3 more Smart Citations
“…For a variety of philosophical, legal, social, budgetary, and educational reasons, special educators are advocating for students with disabilities to be educated alongside their peers without disabilities in general education classrooms. Although some authors have found that the performance of students with disabilities in inclusive classrooms equals or surpasses their performance in pullout settings (e.g., Rea, McLaughlin, & Walther-Thomas, 2002), the results of this study support other authors who warn that even in general education classes with small groups of students, some students with disabilities do not get the individualized attention they need to understand the academic content (Baxter, Woodward, Voorhies, & Wong, 2002, Bottge et al, 2002Kauffman, 1999).…”
Section: Practical Significancesupporting
confidence: 75%
“…The content validity of the tests was supported by their use in previous studies (e.g., Bottge, 1999;Bottge & Hasselbring, 1993;Bottge et al, 2002) and by previous research showing that the test items reliably estimated mathematics achievement (Cohen, Bottge, & Wells, 2001). We calculated the interrater reliability of each measure on 20% of the test protocols from a randomly selected sample of pretests and posttests by dividing the number of agreements by the total number of agreements and disagreements and multiplying by 100 (Sulzer-Azaroff & Mayer, 1977).…”
Section: Research Design and Instrumentationmentioning
confidence: 66%
See 2 more Smart Citations
“…Studies have found cue cards (Joseph & Hunter, 2001), mnemonic devices (Test & Ellis, 2005), and schema based instruction (Xin, Jitendra, & Deatline-Buchman, 2005) to be effective interventions for students with LD. Several other studies (Bottge, 1999;Bottge & Hasselbring, 1993;Bottge, Heinrichs, Mehta, & Hung, 2002;Bottge et al, 2010) have focused on using contextualized or anchored instruction to improve students' problem solving skills. Results of this line of research seem to show the most promise when the contextualized instruction is paired with extra instruction (e.g., Mastery Fractions videodisc program).…”
Section: Fraction Performance Of Students With Disabilitiesmentioning
confidence: 99%